Analysis Of The Quality Of Ice Cream With Substitution Of Katuk Leaf Extract - Afrilla, Sindy; Faridah, Anni (Universitas Negeri Padang, 2023)
Ice cream is a food that is loved by all people. Ice cream is a food product that contains milk fat and protein. In making ice cream, we still use synthetic dyes, even though there are many natural dyes around us, which have many benefits. So the purpose of this research is to substitute katuk leaf extract in making ice cream. The type of research used was a pure experiment (true experiment), using a Completely Randomized Design (CRD) with 3 repetitions. The data collection technique was carried out by giving questionnaires to limited panelists who were lecturers in Family Welfare with a concentration in Culinary Planning, Padang State University. Data were analyzed using Analysis of Variance (ANAVA), if Fcount > Ftable then proceed with Duncan's Test. The results showed that there was a significant effect on color quality with a value of 3.83 (X3). Overall the best quality analysis results were found in treatment X2, namely the addition of 25% katuk leaf extract